Integrating Prophetic Teaching Methods into 21st-Century Islamic Education: A Systematic Review of Pedagogical Practices from Sirah Nabawiyah - Rafiq-uz-Zaman, Muhammad; Nadeem, Muhammad Asif (Journal for Teaching and Education for Scholars, 2026)
This review study focuses on the prophetic pedagogical approaches based on the Sirah Nabawiyah and its modern use in Islamic studies. This review summarizes the findings of 50 peer-reviewed studies (including those across different geographic settings) and systematically organizes 4 main areas of prophetic pedagogical practice: verbal/cognitive methods (questioning, storytelling, parables), demonstrative methods (role modeling, hands-on practice), affective/motivational methods (encouragement, emotional support), and evaluative methods (feedback, holistic Modern findings have also revealed that these pedagogical methods which have their origins in history continue to be incredibly effective in addressing challenges of the 21st century. The approaches are effectively used in curriculum design, character education, information technology integration, and teacher training among students in traditional Pesantren, integrated Islamic, and international academic institutions. This pedagogical system is an integrative, prophetic approach to human development, which focuses on the spiritual, moral, intellectual, and social aspects of human development and offers an alternative, theoretically consistent approach to education, rather than the secular models of education. Limited capacity of the teachers, infrastructural limitations, and the need to balance the traditional Islamic values with the competencies of the 21st century are among the most challenging problems. Theoretically, this review helps conceptualize prophetic pedagogy as a unique paradigm of education, practically to the structure of implementation in institutions and educational leaders and policy-wise to the advice on evidence-based recommendations on Islamic educational leaders. New studies will involve intensive empirical studies, cross-cultural comparative study, and systematic exploration of technology adoption and still maintain the originality of Islamic education.